Discovery of a Novel ERp57 Inhibitor as Antiplatelet Agent from Danshen (Salvia miltiorrhiza). (24th April 2018) - Zou, Jia; Chen, Yang; Hoi, Maggie Pui Man; Li, Jun; Wang, Tao; Zhang, Ying; Feng, Yu; Gao, Jianli; Lee, Simon Ming Yuen; Cui, Guozhen
Abstract : Danshen (Salvia miltiorrhiza) is a well-known herb in Traditional Chinese Medicine (TCM) for treating cardiovascular diseases, but the underlying mechanism remains to be fully elucidated. Here, we showed that Danshen and its active ingredient rosmarinic acid exhibited antiplatelet effects through the inhibition of ERp57, a member of protein disulfide isomerase (PDI) with potential roles in platelet aggregation. Danshen extract (DSE) exhibited potent inhibitory effects on the platelet aggregation induced by arachidonic acid- (AA-) induced platelet aggregation and the enzymatic activity of ERp57. Rosmarinic acid was identified by virtual screening and molecular docking as one of the hit compounds for ERp57. In line with this, rosmarinic acid displayed significant inhibitory effect on ERp57 activity and inhibited AA-induced platelet aggregation. Taken together, we demonstrated for the first time that DSE and rosmarinic acid displayed inhibitory effects on the catalytic activity of ERp57, providing evidence of the regulatory role of ERp57 underlying the antiplatelet effects of Danshen.